2018
DOI: 10.1002/jcp.27474
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol burden in the liver induces mitochondrial dynamic changes and resistance to apoptosis

Abstract: Non-alcoholic fatty liver disease (NAFLD) encompasses a broad spectrum of histopathological changes ranging from non-inflammatory intracellular fat deposition to non-alcoholic steatohepatitis (NASH), which may progress into hepatic fibrosis, cirrhosis, or hepatocellular carcinoma. Recent data suggest that impaired hepatic cholesterol homeostasis and its accumulation are relevant to the pathogenesis of NAFLD/NASH. Despite a vital physiological function of cholesterol, mitochondrial dysfunction is an important c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 29 publications
2
50
0
4
Order By: Relevance
“…(Koh et al ; Klein et al ; Kennedy et al ) Most workers attribute this respiratory impairment not to loss of cyt c , or structurally aberrant mitochondria more generally, but to excess mitochondrial cholesterol poisoning the organelle. This hypothesis is superficially appealing and also consistent with mitochondrial dysfunction induced by cholesterol over‐feeding in hepatic (Domínguez‐Pérez et al ) and pancreatic (Asalla et al ) cells. Perhaps significantly, increased contacts between mitochondria and endosomes, and correspondingly decreased contacts between ER and endosomes, have recently been reported in NPC1‐deficient cells (Höglinger et al ).…”
Section: Npc1supporting
confidence: 65%
“…(Koh et al ; Klein et al ; Kennedy et al ) Most workers attribute this respiratory impairment not to loss of cyt c , or structurally aberrant mitochondria more generally, but to excess mitochondrial cholesterol poisoning the organelle. This hypothesis is superficially appealing and also consistent with mitochondrial dysfunction induced by cholesterol over‐feeding in hepatic (Domínguez‐Pérez et al ) and pancreatic (Asalla et al ) cells. Perhaps significantly, increased contacts between mitochondria and endosomes, and correspondingly decreased contacts between ER and endosomes, have recently been reported in NPC1‐deficient cells (Höglinger et al ).…”
Section: Npc1supporting
confidence: 65%
“…Although mitochondria are cholesterol-low organelles, several lines of studies have reported that cholesterol levels of mitochondria isolated from hepatic cancer cells are elevated and that this phenomenon is correlated with resistance to apoptotic cell death [37][38][39]. In addition, compared with chow diet-fed mice, hepatocytes from high-cholesterol-dietfed mice increase levels of not only pro-apoptotic Bax protein but also anti-apoptotic proteins, Mcl-1 and Bcl-xL as a compensatory anti-apoptosis response [39].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial cholesterol accumulation is a hallmark of chronic diseases, including cardiovascular disorders, cancer and Alzheimer's disease [[21], [22], [23], [24], [25], [26], [27], [28]]. In addition, previous studies have shown an association between increased mitochondrial cholesterol levels and liver injury in alcoholic and nonalcoholic liver disease [[29], [30], [31], [32], [33], [34]]. However, the specific role of mitochondrial cholesterol accumulation in mitochondrial respiration and organization of functional respiratory complexes has not been previously examined.…”
Section: Introductionmentioning
confidence: 99%